USE OF THE SWOT-ANALYSIS METHODS IN DEVELOPING THE INTERNATIONALIZATION STRATEGY OF HIGHER EDUCATION INSTITUTIONS - Verbovska, L. S.; Stepanyuk, H. S.; Kushlyk, O. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article substantiates the influence of globalization processes on the development of institutions of higher education that take place in the world. The foreign countries universities experience of internationalization processes is considered. The concept of strategic management as an effective technology of higher education institutions management, particularly in the sphere of international activity and the necessity of carrying out the university diagnostics using existing strategic analysis tools, is substantiated. The potential advantages and opportunities provided by the internationalization strategy for the development of domestic institutions of higher education are determined. The development of the university internationalization strategy is based on the development of students international academic mobility and scientific and pedagogical workers, stimulation of educational programs and scientific researches joint with foreign partners, which ensure the implementation of productive mechanisms for the integration of the higher education domestic institutions into the global scientific and educational environment. The main factors influencing the formation of the internationalization strategy and the principles on which the development of such a strategy for modern universities is based are established. The SWOT-analysis of domestic universities has been conducted and the main results of the research based on the strengths and weaknesses, opportunities and threats of the international activity of higher education institutions are presented. This methodology of SWOT-analysis during developing the internationalization strategy allows combining the procedure of analytics and the procedure of choosing strategic alternatives. The SWOT-analysis matrix of strategic alternatives has been used to help the management of higher education institutions in formulating the internationalization strategy in the field of university international cooperation, which can be applied in such areas as internationalization of educational activities, internationalization of scientific activity, internationalization of social development. The main tasks of internationalization in Ukrainian higher education institutions and the expected results from the implementation of internationalization strategies in domestic universities are singled out.